Farmers’ knowledge, practices and use of sesame genetic resources in the production systems of Benin: case study of agro-ecological zone IV - EZIN, VINCENT; Sanni, Gazali B.T.A.; AHANCHEDE, ADAM (My University, 2022)
Sesame (Sesamum indicum L.) is an important crop cultivated for its grains, which demand is constantly increasing in Africa. In Benin, sesame is produced on a small area despite its high economic potential. The overall objective of this study was to reinforce local knowledge (cultural methods) related to the management of different Sesamum indicum cultivars in Benin's Agro-ecological Zone IV. A total of 273 producers were surveyed using the nonprobabilistic snowball method supported by systematic census. The typological analysis consisted of a Multiple Correspondence Analysis (MCA) and a Hierarchical Ascending Classification (HAC) using RGui.4.1.0 software. The result of the MCA revealed four types of sesame production systems based on several variables. The characterization of the producers of each production system according to the townships showed that there was a dependency relationship between the production systems and the townships. 100% of producers in the township of Cobly used the traditional production system (Type IV). 94.7% of producers in Materi township practiced the modern production system (Type I). The different cultural methods for sesame production varied from one ethnic group to another. The Wama and Mossi ethnic groups practiced the modern semi-intensive production method (Type II). The conservative production system (Type III) was specific to the Ditamari. 61.8% Farmers planted sesame in August and 56.1% farmers harvested in October. Only 0.6% of respondents applied mineral fertilizer for sesame production. The number of cultivars used per village varied from 2 to 4 with an average of 2 over the entire study area. Toucountouna and Materi had the most diversity with the largest number of cultivars (03) each. Only 1 cultivar was obtained Tanguieta. Sesame processing is low throughout the study area. Sesame cultivation can be intensified because of its low production costs.
Keywords: Cultivation systems; Indicum; Cultivation practices; Producers; Atacora